2013
DOI: 10.1002/eco.1428
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of the total evapotranspiration in a Japanese cypress plantation during the growing season

Abstract: We investigated the contribution of three evapotranspiration (ET) components including canopy interception (Ei), tree transpiration (Et) and forest floor evaporation (Ef) and identified the sources depth of evaporated water in a Japanese cypress stand. Monitoring primarily focused on the growing season of July–October 2011. In a 12 × 13 m plot with 28 trees with a DBH of 19.1 ± 3.9 cm, Ei was calculated as the difference between precipitation on an open field and precipitation under a canopy as the sum of thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 43 publications
2
28
0
Order By: Relevance
“…In addition, our E c estimates may not be accurate for cases in which forest management is conducted in an untraditional way. For example, several scholars (e.g., Nanko, Onda, Kato, & Gomi, ; Sun, Onda, Kato, Otsuki, & Gomi, ; Sun, Onda, Otsuki, et al, ) recently propose intensive thinning of forests (~50% of the stem density) to secure water resources. To reasonably estimate E c for these cases, it is necessary to create yield tables for intensively thinned cypress forests and to confirm validity of assuming constant u ref among stands.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our E c estimates may not be accurate for cases in which forest management is conducted in an untraditional way. For example, several scholars (e.g., Nanko, Onda, Kato, & Gomi, ; Sun, Onda, Kato, Otsuki, & Gomi, ; Sun, Onda, Otsuki, et al, ) recently propose intensive thinning of forests (~50% of the stem density) to secure water resources. To reasonably estimate E c for these cases, it is necessary to create yield tables for intensively thinned cypress forests and to confirm validity of assuming constant u ref among stands.…”
Section: Discussionmentioning
confidence: 99%
“…Monthly Δ S (mm) in 0–180 cm profile was calculated according to initial and final SWC of each growing season (Wang et al ., ). ET and its components can be expressed as ET=Ei+Ec+Es where E i is canopy interception, E c is canopy transpiration and E s is soil evaporation (Sun et al ., ).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, tree transpiration was reported to be associated with soil-water content at a depth of 10~20 cm in a semi-arid pine forest [39]. Sun et al [40] found that in a humid forest, transpiration was related to soil moisture at a depth of 5~15 cm and soil evaporation was generally related to soil moisture in the topsoil (5 cm depth). The seasonal pattern of soil-water content at our site was similar to these previous studies.…”
Section: Meteorological and Soil-water Conditionsmentioning
confidence: 99%